Identificación de la hesperidina aislada del albedo de citrus Paradisi macfadyen (pomelo) por sus características fisicoquímicas y espectrometría UV - Gárate Ruiz, Aydee Rosa Esperanza (2023)
The objective of this research was to identify the hesperidin isolated from the albedo of Citrus paradisi Macfadyen by estimating the physicochemical and spectrometric ultraviolet-visible characteristics. The albedo of the species was collected in the town of Padre Cocha, Punchana, Maynas and Loreto. It was dried and then pulverized, passed through 60 mesh ASTM, two hundred grams of sample were macerated in an alcohol-water system (1:1) and 10% calcium hydroxide solution in ethanol (8:2), filtered under reduced pressure, concentrated, and left to stand, precipitating amorphous yellow crystals, purified by washing with distilled water +several times on filter paper precipitating white crystals in the form of needles. Measurements of hysicochemical characteristics were: Melting point 262 °C, Specific rotation [] 23 = −76 ° in pyridine, showed solubility in pyridine, formamide, and dimethylformamide; by RAST method the molecular weight was 610,581 g/mol; Rf values in two-dimensional paper chromatography run on tert-butyl acetate (TBA) and acetic acid (HOAC) gave 0.51 and 0.78 respectively; Spectrometric measurement on UV equipment gave the following maximum wavelengths: 283 and 327 nm using methanol as the displacement reagent, and in sodium acetate and methanol 284 and 328 nm were obtained. These values are similar to those reported in the literature for hesperidin. Consequently, the substance isolated from the albedo of C. paradisi Macfadyen is hesperidin.